Benefits and Challenges of Diploma Level Educational Programs in India - Monia Dixit, (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2013)
The world has realized that the monetary outcome of the states still up in the air by their schooling systems. Schooling is a Nation's Strength. A created country is unavoidably an informed country. Indian advanced education framework is the third biggest on the planet, close to the United States and China. Since freedom, India as an emerging country is petulantly advancing in the schooling field. In spite of the fact that there have been part of difficulties to advanced education arrangement of India however similarly have parcel of chances to defeat these difficulties and to make advanced education framework much better. It needs more noteworthy straightforwardness and responsibility, the job of schools and colleges in the new thousand years, and arising logical exploration on how individuals procure is of most extreme significant. India need well gifted and profoundly taught individuals who can drive our economy forward. India gives exceptionally gifted individuals to different nations in this way; it is extremely simple for India to move our country from an agricultural country to a created country. The ongoing review plans to feature the difficulties and to bring up the potential open doors in advanced education framework in India.